2018
DOI: 10.15593/perm.mech/2018.2.03
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the Structure of Disperse-Filled Polymer Composites

Abstract: . Formation of the properties of the structure of disperse-filled polymer composites. PNRPU Mechanics Bulletin, 2018, no. 2, pp. 24-31. DOI: 10.15593 В работе исследовано влияние структуры на свойства металлополимерного композита, состоящего из полимерной матрицы в виде эпоксидной смолы (ЭД-20) с бутадиен-стирольным каучуком (БСК), дисперсно-наполненной частицами наномеди. В рамках фрактального анализа рассчитан реальный диаметр агрегатов исходных частиц наполнителя при различных степенях концентрации и размер… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…To describe the structural features of the nanocomposite under study, a cluster model of the structure of the amorphous state of polymers was used [4]. This model assumes that in the amorphous state of the polymer, along with a grid of macromolecular "entanglements", there is a cluster mesh of meshes consisting of regions of local order (clusters) immersed in a loosely packed (or, what is the same, loosely packed) matrix.…”
Section: Results Of the Study Of The Process Of Structure Formation I...mentioning
confidence: 99%
See 1 more Smart Citation
“…To describe the structural features of the nanocomposite under study, a cluster model of the structure of the amorphous state of polymers was used [4]. This model assumes that in the amorphous state of the polymer, along with a grid of macromolecular "entanglements", there is a cluster mesh of meshes consisting of regions of local order (clusters) immersed in a loosely packed (or, what is the same, loosely packed) matrix.…”
Section: Results Of the Study Of The Process Of Structure Formation I...mentioning
confidence: 99%
“…According to the cluster model, a mesh polymer consists of two componentsa loosely packed (or, what is the same, weakly packed) matrix and nanoclusters, the latter playing the role of a nanofiller, and a loosely packed matrix − the role of a matrix of a natural nanocomposite. In [4], based on fractal estimates of the surface of nanoclusters, the dependence of the volume fraction of the loosely packed matrix on the temperature of the composite was found. It is shown that the dimensional effect of nanoclusters is identical to the corresponding effect of dispersed filler in artificial polymer nanocomposites, namely, a decrease of the number of statistical segments in one cluster or the radius of clusters increases the degree of amplification (modulus of elasticity) of the artificial nanocomposite [5].…”
Section: Introductionmentioning
confidence: 99%
“…As one of kinds of a material the composition on a basis ftoroplast marks FТ4А and composite material (SКN4О+SKEPT60+PVCH10) was used. As fillers were taken: graphite PG-1 and nano-copper, with sizes of 60-80 nm [8,9].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…The laboratory testing technique was carried out according to the recommendations [8,9], which examined almost the entire set of modern methods used for testing polymer materials.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…Фрактальная размерность поверхности частиц наполнителя н d и реальный диаметр агрегата частиц наполнителя D ag были определены нами в работе [24].…”
Section: оценка структурных особенностей межфазного слоя полимерных нанокомпозитовunclassified